9.9k views
0 votes
9(p−4)=−18 p= I am not great at math, please explain just a little bit

User Miszmaniac
by
5.6k points

2 Answers

0 votes

Answer:


\large \boxed{{p=2}}

Explanation:

9(p-4) = -18

Expand brackets.

9p -36 = -18

Add 36 on both sides.

9p -36 + 36 = -18 + 36

9p = 18

Divide both sides by 9.

(9p)/9 = 18/9

p = 2

User Nikki Locke
by
5.7k points
2 votes

Answer:

p = 2

Explanation:

9(p - 4) = -18

You are solving for the variable, p. Note the equal sign, what you do to one side, you do to the other. Do the opposite of PEMDAS.

PEMDAS is the order of operation, and =

Parenthesis

Exponents (& Roots)

Multiplication

Division

Addition

Subtraction

~

First, divide 9 from both sides:

(9(p - 4))/9 = (-18)/9

(p - 4) = -18/9

p - 4 = -2

Isolate the variable, p. Add 4 to both sides:

p - 4 (+4) = -2 (+4)

p = -2 + 4

p = 4 - 2

p = 2

Check. Plug in 2 for p in the equation:

9(p - 4) = -18

9(2 - 4) = -18

9(-2) = - 18

-18 = -18.

~

User Mflodin
by
6.0k points